2008
DOI: 10.4315/0362-028x-71.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Washing Practices on the Microflora on Georgia-Grown Cantaloupes

Abstract: In recent years, several foodborne illness outbreaks have been associated with the consumption of cantaloupe. Cantaloupes can be contaminated with pathogens anywhere from the field to the packing line. In the United States, cantaloupes are handled and packed differently in each state. Georgia-grown cantaloupes are brought to sheds, washed, and packed, whereas California-grown cantaloupes are field packed. In this study, the microbiological status of cantaloupes produced by four Georgia growers that use various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Akins et al (2008) reported that cantaloupe taken from the wash tank exhibited lower microbial counts than cantaloupe taken after conveyor belts in the packaging area of the processing plant. This suggested that the conveyor belts may have contributed to recontamination of the cantaloupe.…”
Section: Prevention Of Pathogen Recontamination and Growth By Packagingmentioning
confidence: 99%
“…Akins et al (2008) reported that cantaloupe taken from the wash tank exhibited lower microbial counts than cantaloupe taken after conveyor belts in the packaging area of the processing plant. This suggested that the conveyor belts may have contributed to recontamination of the cantaloupe.…”
Section: Prevention Of Pathogen Recontamination and Growth By Packagingmentioning
confidence: 99%
“…; Ukuku and Fett ; Akins et al . ), but other research has reported some negative quality attributes of melons. Fan and group (2009) found fungal reductions after sanitizing melons with peroxyacetic acid at 80 ppm, but noted sensory reductions of aroma and appearance.…”
Section: Introductionmentioning
confidence: 94%
“…In California melons are harvested and packed in the field, but in Georgia, the harvested melons are transported to a shed for washing and packing (Akins et al, 2008). In Mexico, cantaloupes are handled in a similar way as in Georgia, according to guidelines for the voluntary implementation of good agricultural practices and good management practices in the production and packing of fruits and vegetables for fresh consumption by humans, released by the Mexican Government (SENASICA, 2008) published after the MOU between the FDA and the Mexican government (Anon, 2005).…”
Section: Potential Sources and Mechanisms Of Contamination And Measurmentioning
confidence: 99%
“…It is believed that contamination of fresh-cut melon results from transfer of human pathogens on the surface to the interior flesh during cutting . As with lettuce and tomatoes, efforts to decontaminate whole cantaloupes by application of sanitizers have achieved limited success (Akins et al, 2008;Fan et al, 2009). Typically, 1-3-log reductions have been reported for cantaloupes inoculated with Salmonella spp.…”
Section: Cantaloupementioning
confidence: 99%